Responses in growth, yield and cob protein content of baby corn (Zea mays L.) to amendment of an acid sulphate soil with lime, organic fertiliser and biochar - Loan, Thi; Yunusa, Isa; Rab, Abdur; Zerihun, Ayalsew; Nguyen, Hoa (Commonwealth Scientific and Industrial Research Organization Publishing, 2022)
Cropping of acid sulfate soils requires effective treatment of their inherently low pH. We evaluated the efficacy of applications of two levels of lime (0 or 2 Mg/ha), two levels of organic fertiliser (0 or 5 Mg/ha), and three levels of biochar (0, 10 or 30 Mg/ha) in a factorial design for ameliorating acidity in an acid sulfate soil, and measured the subsequent growth and yield of baby corn (Zea mays L.). Lime increased soil pH(H2O) from 3.75 to 4.12, salinity from 1.72 to 1.95 dS/m, and cob yield by 30%. None of the amendments significantly altered total organic carbon or total nitrogen concentrations in the soil. Biochar additions increased cob yields by an average of 28% on both unlimed and limed soil. Addition of organic fertiliser increased cob yield by 45% on unlimed soil but had no significant effect on yields on limed soil. The yields obtained with liming were similar to the highest yields achieved with biochar or organic fertiliser applied either separately or in combinations. Overall, cob yields were increased by 19% with addition of organic fertiliser. The yield increseas from additions of biochar or organic fertiliser were associated with improvements in nutrient supply. However, the increases in cob yield were associated with reduced cob protein, probably resulting from poor availability of nitrogen late in the season. We conclude that biochar and organic fertiliser applied in relatively large quantities can be viable treatments for cropping acid sulfate soils.